FRI0431 EFFECT OF PHOSPHODIESTERASE 4 INHIBITION WITH APREMILAST ON BODY WEIGHT AND VASCULAR FUNCTION IN PSORIATIC ARTHRITIS – INITIAL RESULTS FROM THE IMMUNE METABOLIC ASSOCIATIONS IN PSORIATIC ARTHRITIS (IMAPA) STUDY. (June 2019) - Ferguson, Lyn D.; Welsh, Paul; Sattar, Naveed; Mcinnes, Iain; Siebert, Stefan
Abstract : Background: Psoriatic arthritis (PsA) is associated with obesity and increased cardiometabolic risk. Weight loss is associated with improved disease activity and has been noted with the phosphodiesterase 4 (PDE4) inhibitor apremilast. Objectives: To investigate the effects of PDE4 inhibition with apremilast on body weight, vascular function and disease activity in psoriatic disease. Methods: The Immune Metabolic Associations in Psoriatic Arthritis (IMAPA) study is a prospective, open label study of adults receiving apremilast 30mg BD as part of routine care for psoriasis and/or PsA. Cardiometabolic, anthropometric, and disease activity assessments were performed at baseline, months 1, 3, and 6. A subgroup underwent endothelial function assessment by Endo-PAT at baseline and month 3. Repeated measures mixed models were used to compare changes in body weight, waist circumference, systolic & diastolic BP, reactive hyperaemia index (RHI), and disease activity markers with apremilast. Results: 53 participants were recruited; mean age (SD) 52 (13) years, 64% female, mean disease duration (SD) 9.3 (8.1) years. To date, data available for n=47 at month 1, n=42 month 3, and n=29 at month 6. Mean weight loss after 6 months apremilast was -1.9kg (95% CI -2.8, -1.0); 13% (7/53) lost ≥5% body weight. Statistically significant improvements in 66/68 joint count, DAS28-ESR, PtGA, PGA, pain-VAS, LEI, and ESR were seen at month 6. There was no statistically significant change in RHI, SBP, or DBP (table 1 ). Weight change showed no statistically significant correlation with change in joint or skin disease activity markers. Conclusion: Apremilast was associated with modest weight loss and reduced disease activity over 6 months. There did not appear to be any significant alteration in endothelial function, however this was assessed in relatively small numbers and many patients had baseline results within normal range. Improvements in disease activity with apremilast appear largely independent of weight change in this cohort. Acknowledgement: Celgene; BHF (RE/13/5/30177). Disclosure of Interests: Lyn D. Ferguson: None declared, Paul Welsh: None declared, Naveed Sattar Grant/research support from: Boehringer Ingelheim, Consultant for: Eli Lilly, Boehringer Ingelheim, Janssen, Novo Nordisk, Sanofi, Speakers bureau: Eli Lilly, Boehringer Ingelheim, Janssen, Novo Nordisk, Sanofi, Iain McInnes Grant/research support from: AstraZeneca, Celgene, Compugen, Novartis, Roche, UCB Pharma, Consultant for: AbbVie, Celgene, Galvani, Lilly, Novartis, Pfizer, UCB Pharma, Stefan Siebert Grant/research support from: AbbVie, Novartis, Pfizer, Janssen, BMS, Celgene, UCB, and Boehringer Ingelheim, Consultant for: AbbVie, UCB, Pfizer, Janssen, Boehringer Ingelheim, Celgene, and Novartis, Speakers bureau: AbbVie, UCB, Pfizer, Janssen, Boehringer Ingelheim, Celgene, and Novartis